Proof of State Financial Losses in State-Owned Banking Enterprises Related to Corruption Crimes - Rahmat Fajri; Ida Keumala Jeumpa; Yusri Yusri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Eradication of Corruption Crimes (Tipikor Law) requires the existence of state financial losses as an important element in Article 2 paragraph (1) and Article 3. Following Constitutional Court Decision No. 25/PUU-XIV/2016, proof of state losses must be actual losses, rather than potential losses. However, in practice, there is a discrepancy between legal norms and the reality of law enforcement, especially in state-owned enterprises (SOEs) engaged in banking. There is disharmony between the Anti-Corruption Law, the State Finance Law, and the SOE Law, particularly regarding the financial status of SOEs as separate state assets. This study uses a normative legal method with a statute approach. The results show that proving state financial losses in banking SOEs related to corruption requires an examination by an authorised institution to declare state financial losses. Based on Article 10 paragraph (1) of Law No. 15 of 2006 concerning the Audit Board, it is explained that the Audit Board has the authority to determine the existence or absence of state losses. The audit process carried out by the Audit Board on state-owned banking enterprises suspected of causing state financial losses must be an investigative audit process, not a state loss calculation audit that is usually carried out on government institutions.